Hubungan Tingkat Kecemasan Terhadap Kekambuhan Gastritis Pada Mahasiswa Tingkat Akhir - Manuntungi, Andi Ernawati (Asosiasi Guru dan Dosen Seluruh Indonesia, 2023)
Health problrms are often underestimated by society, especially ypung people, especially among students. This matter because their daily livers are busy with their daily activities for example school acyivities, therefore starr to feel anxious so they don’t pay much attention to the type of food they eat, common causes of gastritis include pattern improper eating,such as the frequency or timing of eating at inappropriate times appropriate, gastritis can easily attack individuals who having an irregular eating pattern.one of the diseases currently common among people experienced by students is gastirits.apart from that, there are various life problems the unresolved makes them range against gastritis. The aim of this research is to determine the level anxiety and the relationship between anxiety levels and recurrence gastritis. this research is quantitative research with a cross sectional approach at IKB St. Fatimah Mamuju. Sample used in this research were 33 people who had meet the inclusion and exclusion criteria. The data that is measured is level of anxiety and recurrence of gastritis. univariate analysis on this research are gender, age, history of gastritis, educations, the biavariate analysis used was the chi square test. Kolmogrov smirnov test for the relationship between anxiety and gastritis recurrence. The bivariate analysis used was the chi square test. Kolmogrov smirnov test for the relationship between anxiety and gastritis recurrence. The results of bivariate analysis show that the level of anxiety not associated with gastritis recurrence (p value 0,0995). So it can be concluded from this research that there is no relationship significant relationship between the level of anxiety and the recurrence of gastritis.